ENVIRONMENTAL MANAGEMENT AND SUSTAINABLE DEVELOPMENT IN NIGERIA: CHALLENGES, POLICIES AND PROSPECTS - Eyisi, Emmanuel Chimezie; Agha, Emmanuel Obiahu; Uzor, Doris Chidiebere (African Journal of Social and Behavioural Sciences, 2025)
This paper focused on the Critical Assessment of the nexus between Environmental Management and Sustainable Development in Nigeria, exploring how the nature of the policies on the environment can make or mar development efforts. The following specific objectives guided the study: To explore the nature of the Nigerian environmental crises in Nigeria; to examine the challenges posed by the state of the environment on sustainable development in Nigeria, and to assess the effectiveness of policy direction of the environmental regulation agencies in the mitigation of environment crises in Nigeria. The paper being qualitative and theoretical critically reviewed and reformulated existing data from the ministries and agencies of government as well as journals and internet sources to interrogate the critical issues in the study. Key findings indicate the increasing deterioration of the Nigerian situation as illustrated in unprecedented drought engendered by deforestation, massive oil-related pollution through unabated oil spillages over land and water and the consistent gas flares, devastating flooding in recent years across the country and mining related environmental degradation; secondly, the underdevelopment crises triggered by the environmental degradation has intensified poverty, hunger, displacement and conflicts across the country; and thirdly, the weak and inconsistent environmental policy initiatives as well as the lacklustre enforcement capacity of the environmental regulatory agencies have unwittingly exacerbated both environmental and the underdevelopment crises the Nigerian Nation is facing. The study recommends the enhancement of institutional capacity in environmental management; the pursuit of development infrastructure underpinned by environment safety, achievement should be the responsibility of government agencies and the Non-Governmental Organisations (NGOs) advocacy in environmental cleanliness; policies that will be in line with International Environmental regulations and Sustainable Developmental Goals (SDGs) should be enunciated to enhance robust Green Economy as well as meet SDG targets for societal sustainable development in Nigeria